(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Ayurved system mainly deals with digestion and associated metabolic methods. Liver i.e. Yakrita is the Moolasthana of Pachak Pittas, Raktavaha strotasa. Which we can correlate with Hepatobiliary system. Disturbance or diseases of hepatic system leads to mortality all the way through failure of remaining systems of our body. Kamala is one of the most important and specified disease of Yakrita which can be correlated with Hyperbilirubinemia or Jaundice. Hyperbilirubinemia is a primary sign of disturbed Liver function. Liver disease is 8th leading cause of death worldwide. 50% of patients with Liver cirrhosis and 70% with cirrhosis plus alcoholic hepatitis die within 48 months. Overall, cirrhosis is the 4th leading cause of death. The overall mortality of acute viral hepatitis is 0.5% under the age of 40 yrs. and 3% in patients over 60 yrs. In which mortality rate of HAV and HEV is 0.5%, HBV is less than 2% and that of HCV is 0.5 -1%. Most of the patients develop chronic infection after acute hepatitis which continues for lifetime. Taken as a whole Hepatitis not only disturbs mental, physical health of patient but also social, economical, cultural and family life of a person. In present study Dhatri Loha Yoga from Ayurvedic granthas tested along with proven efficient drug Kutki over Kamala (Hyperbilirubinemia). Dhatri Loha Yoga is a combination of drugs which directly deals with bilirubin metabolism. Dhatri LohaYoga significantly reduces symptoms of Kamala upto 94.2 % which is very favorable. It shows reduction in Sign, Symptoms, and Specific biochemical markers like SGPT, SGOT, and Serum Bilirubin. From the statistical analysis through Chi-square Test the two-sided P value is < 0.0001, Thus Dhatri loha yoga is extremely significant in the management of Kamala and regulating bilirubin metabolism.